Research method for management of thermoplastics production improvement in rubber industry with the use of 3D simulation modeling - Sándor Forrai; Balázs Ludanyi; István Péter Szabó; Justyna Smagowicz; Cezary Szwe (Foundations of Management, 2021)
The paper concerns research and improvement of production processes in one of the European companies in the rubber industryThe company did not allow the name or country to be given.. The main goal is to improve the production process of the thermo-plastics obtained from polymer materials on the company's production line. Improvement is defined as a reduction of the setup time of a key machine in the tested production process. The research method includes the analysis of the literature, observation of the studied process, and the accomplished computer simulation experiments. The proposed activities relate to the reinforcement of the key part of the machine, the change of the machine setup method, and the preliminary staff assignment to the specific tasks. The results of the simulation experiments confirm the implementation of the proposed improvements. The theoretical contribution to the research field development is the proposal of the simulation modeling methodology to improve production processes of continuous materials. Practical conclusions lead to recommendations for the implementation of improvements in the enterprise, with direct application of the proposed actions.
Keywords: C6; D2; L6; 650; production management; simulation modeling; improvement of production processes; SMED; rubber industry; calender